Surgical Management of Gunshot Wound at Level-II Hospital in Central African Republic in 2019/2020 (Community Based Medical Journal, 2022)
Background: Gunshot wounds (GSW) are common in Central African Republic (CAR). There are about eighteen rebel groups in Central Africa. Arms are available among the rebel groups and also the civilians. For the very simple region they open the fire against the opponent. The aim of this study is outcome of surgical management of gunshot wounds at Bangladeshi Level-II hospital in the CAR during our tenure.Methods: This was a prospective study of 14 patients with gunshot wounds who were treated at level-II hospital, Kagabandoro, CAR from Dec 2019 to Nov 2020 for a period of 12 months. Wound debridement and removal of bullets were done in 8 (57.14%) cases, keep bullets in situ position in 2(14.29%) cases and surgical toileting followed by primary closure of wound were done in 3 (21.42%) cases and one female patient transferred to level-III hospital in Bangui.Results: Out of 14 patients there were 13 male and 1 female patients. Mean age of the patients was 32.21 (18-55 years). High velocity injuries were common in 10 (71.43%). Injuries involved the limbs in 10 (71.43%), chest in 2 (14.29%), abdomen in 1 (7.14%) and external genitalia in 1(7.14%). Most of the patients 12 (85.71%) presented to the hospital within 12 hours of the injury. The average length of stay in the hospital was 14 days (Range 2- 60 days). Fractures of the long bone were in 5 (35.71%) cases. Open reduction and internal fixation was done in 3 (21.43%) cases. One female patient was transferred to level-III hospital in Bangui due to fracture neck of femur following gunshot injuries with 9 months of pregnancy. Mean follow-up was 5 months (Range 1-12 months). Post trauma pain developed in 3 (21.43%) cases, deformities of the extremities was found in 2 (14.29%) cases.Conclusion: Outcome of surgical management of the gunshot wounds were depends on the nature of tissue injury and availability of the resources with promptness of intervention.CBMJ 2021 January: vol. 10 no. 01 P: 04-08